Knowledge, attitude and practice on dengue among residents of tribal hostel in Bilaspur: a cross-sectional study - Sharma, Vivek; Parveen, Nasarin; Deissuza, Darwin (International Journal of Research in Medical Sciences, 2024)
Background: In the present era, vector-born disease accounts for 17% of the estimated global burden of all infectious diseases. One such deadly vector-borne disease is dengue. Dengue, dengue hemorrhagic fever, and dengue shock syndrome are major international public health concerns; 2.5 billion people live in high-risk dengue areas with 50 million dengue infections worldwide annually. Aim of the research was to conduct cross-sectional knowledge, attitude and practice (KAP) study of dengue among residents of tribal hostel in Bilaspur, Chhattisgarh (C.G). Methods: A community-based cross-sectional study was conducted among 150 students residing at a tribal hostel of Bilaspur. Results: The study showed that 95% of the participants had previously heard about dengue. Only 34.3% of the respondents were aware that dengue is a contagious disease, and only 48.6% knew that the disease is caused by the bite of mosquito. Almost 52% were aware of the exact source of disease transmission. Conclusions: When it came to basic knowledge about dengue, the majority of the respondents answered positively. However, there were large lacunae present within the specific knowledge of dengue such as, whether dengue is contagious, or about the biting and breeding time and site, respectively, of the mosquito.